1995
DOI: 10.1002/rsa.3240060107
|View full text |Cite
|
Sign up to set email alerts
|

Randomized greedy matching. II

Abstract: We consider the following randomized algorithm for finding a matching M in an arbitrary graph G = (V, E ) . Repeatedly, choose a random vertex u , then a random neighbour u of u . Add edge { u , u ) to M and delete vertices u, u from G along with any vertices that become isolated. Our main result is that there exists a positive constant E such that the expected ratio of the size of the matching produced to the size of largest matching in G is at least 0.5 + e. We obtain stronger results for sparse graphs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
94
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(94 citation statements)
references
References 3 publications
0
94
0
Order By: Relevance
“…All those who had previous aortic surgery and correction of congenital cardiac abnormality in childhood were excluded, as were those operated for infective endocarditis. Of 315 eligible redo patients, we found best matched pairs for 289 on the basis of age, gender, left ventricular systolic function and type of surgical procedure among patients who underwent primary cardiac operation, using the Greedy method [10]. Demographic information, clinical symptoms, comorbidities, operative and postoperative details were retrieved from the database and supplemented with chart review.…”
Section: Study Populationmentioning
confidence: 99%
“…All those who had previous aortic surgery and correction of congenital cardiac abnormality in childhood were excluded, as were those operated for infective endocarditis. Of 315 eligible redo patients, we found best matched pairs for 289 on the basis of age, gender, left ventricular systolic function and type of surgical procedure among patients who underwent primary cardiac operation, using the Greedy method [10]. Demographic information, clinical symptoms, comorbidities, operative and postoperative details were retrieved from the database and supplemented with chart review.…”
Section: Study Populationmentioning
confidence: 99%
“…On the other hand, Aronson et al (1993) can show that (5.2) yields a 1 performance of at least --+ e with e>0.001, where the 2 lower bound is conjectured to be not best possible. Karp and Sipser (1981) have analyzed a greedy heuristic in the spirit of (5.1) that avoids the pitfalls of the worstcase example above: Select, if possible, a vertex with exactly one incident edge at random.…”
Section: Probabilistic Analysismentioning
confidence: 99%
“…Section 5 surveys some results on the probabilistic analysis of greedy algorithms for assignment problems. While most of these results refer to the estimation of the average-case performance, Aronson et al (1993) are able to show that randomization of the greedy algorithm for matching problems helps on concrete graphs. We consider on-line problems in Sect.…”
Section: Introductionmentioning
confidence: 99%
“…This idea was first used by Aronson, Dyer, Frieze, and Suen in [2] where they gave the following randomized algorithm for the maximum matching problem -Pick a vertex at random and match it to one of its unmatched neighbors uniformly at random. They showed that this algorithm does marginally better than 0.5 and attains a factor of 0.50000025.…”
Section: Introductionmentioning
confidence: 99%